The effects of high perinatal sodium chloride exposure on the blood pressure and plasma renin activity response to chronic high sodium challenge in adult rats - Aminuddin, Niferiti; Mohd Noor, Noriah; Mohd Rashid, Muhammad Hakimi; Tin , Myo Han; Azzubaidi, Marwan Saad; Abdul Razak, Tariq (2014)
An insult during a critical period of fetal development may result in increased risk for development of hypertension (Barker & Martyn, 1992). One model of perinatal programming includes the effects of high maternal dietary sodium concentration on the offspring’s blood pressure and plasma renin activity upon short term exposure to low and high salt diet in adulthood ( Da Silva et al. 2003). This study aims at evaluating the effects of high maternal dietary sodium intake during pregnancy and lactation on their offspring’s blood pressure and plasma renin activity at 16 weeks upon 1 month of high dietary sodium challenge in comparison to normal maternal dietary sodium concentration (1.0% NaCl). Normotensive female Sprague-Dawley rats were subjected to timed- pregnancy. Pregnant rats were randomly divided into two groups and were fed normal-sodium diet ( NSD)(1.0% NaCl)( n=10) or high-sodium diet( HSD)(3.0% NaCl)(n=10) during pregnancy and 4 weeks of lactation. The offsprings were weaned at 4 weeks old. Thereafter, both groups were fed with normal-sodium diet (1.0% NaCl) until 12 weeks old and then challenge with 3% NaCl diet for 4 weeks. Blood pressure, heart rate, body weight and daily food intake were measured in the offsprings at 12 and 16 weeks old. There were similar mean daily food intake between week 12-16 (g/day) (22.84±0.09 vs 23.02±0.20 ) and mean body weight (g) at 12 weeks (384.79±2.28 vs 389.73±4.65) and 16weeks (434.55±3.00 vs 443.77±4.46) in the offspring of NSD and HSD dams respectively. At 12 &16 weeks old, the offspring’s mean systolic blood pressure were significantly higher in HSD than NSD dams. No significant differences in mean heart rate at 12 weeks and upon high dietary sodium challenge at 16 weeks in the offspring. Systolic blood pressure and plasma renin activity response to high sodium challenge were similar in the HSD and NSD offspring. HSD offspring have greater propensity to develop higher blood pressure than NSD offspring at 12 and 16 weeks old. The underlying mechanism might not be related to alteration in renin angiotensin system as the plasma renin activity at baseline and upon challenge were similar between HSD and NSD group. The results suggest that there is a similar pattern of blood pressure changes in HSD and NSD offspring upon chronic high dietary sodium challenge. HSD offspring have greater propensity to develop higher blood pressure than NSD offspring at 12 and 16 weeks old.